2017
DOI: 10.4172/2161-1459.1000232
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Vanillin on Indomethacin-Induced Gastric Ulcer in Rats: Protective Pathways and Anti-Secretory Mechanism

Abstract: Indomethacin provokes aggressive ulcerogenic adverse effects. Natural products with fewer side effects are therefore highly requested to attenuate its gastric ulcer effect. Vanillin is a natural compound widely used as flavoring agent which has antioxidant activity. Therefore, the aim of this study was to investigate its gastroprotective effect against indomethacin induced gastric injury. Rats were divided into four groups; first group served as control, group 2: Treated with indomethacin (25 mg/kg, po.), grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Recently, ELBini and Neili [32] demonstrated that the use of a K channel blocker stimulated the process of the myelination of nerve fibers in a model of multiple sclerosis when introduced early during disease development or during remission and exacerbated the demyelination when introduced in a toxic inflammatory environment during the inflammatory processes. Moreover, vanillic acid treatment significantly decreased these inflammatory markers (IL-17, INF-γ) in the sciatic nerve, which is in parallel with the results of Katary & Salahuddin, [33] that vanillic acid downregulates inflammatory cytokines induced by indomethacin in the gastric mucosa. These findings suggest anti-inflammatory actions of VA in the Cuprizone demyelinating rat model.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, ELBini and Neili [32] demonstrated that the use of a K channel blocker stimulated the process of the myelination of nerve fibers in a model of multiple sclerosis when introduced early during disease development or during remission and exacerbated the demyelination when introduced in a toxic inflammatory environment during the inflammatory processes. Moreover, vanillic acid treatment significantly decreased these inflammatory markers (IL-17, INF-γ) in the sciatic nerve, which is in parallel with the results of Katary & Salahuddin, [33] that vanillic acid downregulates inflammatory cytokines induced by indomethacin in the gastric mucosa. These findings suggest anti-inflammatory actions of VA in the Cuprizone demyelinating rat model.…”
Section: Discussionsupporting
confidence: 84%
“…Several lines of evidence have demonstrated the defensive role of NO as a gastroprotective mediator against gastric ulceration through enhancement of mucosal blood flow, stimulation of gastric mucus secretion, and reduction of leukocytic cells' infiltration 5961. Notwithstanding, upregulation or downregulation of NO can cause deleterious gastric mucosal damage 62,63. The marked effectiveness of the medicated COS-NP s could be assigned to the activity of the drug and the polymer in normalizing the upregulated NO content in ulcerated gastric tissue 10,17…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, vanillin and catechin are important phenolic compounds found in geranium. Vanillin decreased stomach levels of Thiobarbituric Acid Reactive Substances (TBARs), Lipid peroxidation byproducts and enhanced GSH and SOD, which affected lipid peroxide levels in gastric tissue, according to Katary and Salahuddin ( 2017 ). Using vanillin as a pretreatment can help reduce stomach acid output.…”
Section: Discussionmentioning
confidence: 95%
“…The antiulcer and gastroprotective effects of Quercetin and its glucosides have also been discovered in numerous studies. Following pretreatment with vanillin, the indomethacin-induced histological changes, free, total acidity levels, ulcer index and gastric juice volume all decreased (Katary and Salahuddin 2017 ). Moreover, catechin showed a potent protective effect against stomach mucosal lesions and reduced the production of histamine, somatostatin, and gastrin.…”
Section: Discussionmentioning
confidence: 99%